O material em suspensão prediz a estrutura da comunidade de amebas testáceas no plâncton de ambientes de uma planície de inundação neotropical? - Costa, Deise de Morais (2012)
The quality of available matter on the aquatic environment is fundamental to many ecological processes. The organic matter is used as a food source, whereas the inorganic matter is essential, for example, for the construction of shells of different organisms. In this context, this study evaluated the relationship between the quantity of suspended matter on the organic and inorganic composition of the test of testate amoebae and the community structure of these protists in different environments of the Paraná River floodplain. A total of 20 samples were taken between February 2006 and December 2010. Were identified 90 infrageneric taxa belonging to nine families, being Difflugiidae, Arcellidae, Centropyxidae Lesquereusiidae the most representative. The analysis of variance (ANOVA), performed to verify differences in suspended matter between lotic and lentic environments, was significant as well as the differences in the community composition, evaluated by the Detrended correspondence analysis (DCA). Analyses of partial redundancies (pRDA) emphasized the importance of suspended matter on the constitution of test and over the community structure. The coefficients of Pearson and Spearman correlations indicated no significant correlations between species richness of endogenous and exogenous tests, and the type of suspended matter. The results indicate that the organic and inorganic suspended matter predict the formation of the test and community structure of testate amoebae.